Training of information technology personnel through simulations for protection against cyber attacks - Basholli, Fatmir; Mema , Besjana; Basholli , Albina (Engineering Applications, 2024)
Nowadays, the development of information technology, robotics and artificial intelligence, has brought radical changes in every aspect of people's lives and this has made our lives have a lot of access to contemporary information and technology. These technological developments in many areas of business and telecommunications, in addition to their benefits, have also increased the risks. Users should be very careful when using social networks, various applications and navigating the Internet world because the risk of cyber-attacks by irresponsible persons with malicious intentions is very frequent. So, web applications make it possible for website visitors to record data or access data through the browser, where all this data is stored in the website's database, which is often the target of cyber-attacks where the attacker has read access, attempts to modify and delete data from the database. This paper aims to provide the necessary information about attacks and cyber hygiene, where we will recommend the review and analysis of these attacks using tools from the MetaSploit library which is a framework that makes hacking easier and is also a tool essential for many attackers and defenders. So MetaSploit helps developers and web administrators from this library to keep up with the times and take preventive measures against the tricks of irresponsible people.